I'm asked to find the volume of the shape that emerges when the curve $y = 14-x^2$ (above $y = 5$) is rotated about the x-axis.

I simply put $14-x^2 = 5$ and got $x=3$ or $x=-3$

From y = 5 we also obtain $f(x) = x^2-9$

So now I want to find $\pi \int_{0}^{3} (x^2-9)^2$ and multiply this by 2 to get the whole volume. I get the volume $\frac{1296\pi}{5}$ from this though, which is incorrect according to my solutions manual. What am I doing wrong?


If you want to use this $$2\pi\int_0^3(9 - x^2)^2dx$$, you need to lift up $x$-axis from $y = 0$ to $y = 5$. Then the areas of the circle (rotated around $x$-axis at y = 5) is the same as integral of the circle of radius $3$ (rotated around the $x$-axis at $y = 0$). However, this time we are asked to rotate $(14 -x^2)$ around $x$-axis$(y = 0)$. We need to subtract inner area(the circle of radius $5$) from total area(the circle of radius $(14 - x^2)$) Therefore, $2\pi\int_0^3(14 - x^2)^2dx$(Total donut) $-$ $2\pi\int_0^3(5)^2dx$(Inner donut). The answer is $\frac{3096}{5}\pi$


The region you are interested in is shown below:

enter image description here

When you rotate that around the $x$-axis, you get a bunch of discs. Can you figure out what the outer and inner radius of each disc is? That should help you develop the proper integral.

Your use of $x^2-9$ as the integrand would be correct if this region rested on the $x$-axis. But the volume you get by rotating the figure above and the volume you get when you rotate a similar region resting on the $x$-axis are not the same.


Well, when you rotate a constant around the x-axis we get:


And for a quadratic equation we get:

$$\mathscr{V}_{\space\text{n}_2,\text{n}_3,\text{n}_4}\left(\text{a},\text{b}\right):=\int_\text{a}^\text{b}\pi\cdot\left(\text{n}_2\cdot x^2+\text{n}_3\cdot x+\text{n}_4\right)^2\space\text{d}x\tag2$$

Now, when we have:


Than we know that:

$$\text{n}_1=\text{n}_2\cdot x^2+\text{n}_3\cdot x+\text{n}_4\space\Longleftrightarrow\space x_{\pm}=\frac{-\text{n}_3\pm\sqrt{\text{n}_3^2-4\cdot\text{n}_2\cdot\left(\text{n}_4-\text{n}_1\right)}}{2\cdot\text{n}_2}\tag4$$


  • $$\text{a}=x_-=\frac{-\text{n}_3-\sqrt{\text{n}_3^2-4\cdot\text{n}_2\cdot\left(\text{n}_4-\text{n}_1\right)}}{2\cdot\text{n}_2}\tag5$$
  • $$\text{b}=x_+=\frac{-\text{n}_3+\sqrt{\text{n}_3^2-4\cdot\text{n}_2\cdot\left(\text{n}_4-\text{n}_1\right)}}{2\cdot\text{n}_2}\tag6$$

For the final volume we get:

$$\mathscr{V}_{\space\text{T}}=\mathscr{V}_{\space\text{n}_2,\text{n}_3,\text{n}_4}\left(x_-,x_+\right)-\mathscr{V}_{\space\text{n}_1}\left(\text{a},\text{b}\right)=$$ $$\int_{x_-}^{x_+}\pi\cdot\left(\text{n}_2\cdot x^2+\text{n}_3\cdot x+\text{n}_4\right)^2\space\text{d}x-\int_{x_-}^{x_+}\pi\cdot\text{n}_1^2\space\text{d}x=$$ $$\pi\cdot\int_{x_-}^{x_+}\left(\left(\text{n}_2\cdot x^2+\text{n}_3\cdot x+\text{n}_4\right)^2-\text{n}_1^2\right)\space\text{d}x\tag7$$

When $\text{n}_2=-1$ and $\text{n}_3=0$, we can simplify $\left(7\right)$, to:

$$\mathscr{V}_{\space\text{T}}=\pi\cdot\int_{-\sqrt{\text{n}_4-\text{n}_1}}^\sqrt{\text{n}_4-\text{n}_1}\left(\left(\text{n}_4-x^2\right)^2-\text{n}_1^2\right)\space\text{d}x=$$ $$\frac{8\pi}{15}\cdot\left(\text{n}_4-\text{n}_1\right)^\frac{3}{2}\cdot\left(3\cdot\text{n}_1+2\cdot\text{n}_4\right)\tag8$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.